Penerapan kebijakan pajak karbon di Indonesia - Sadewo, Bagus; Setiawati Millenium, Errica; Asri Haryanda, Wal; Wulandari, Christine; Bakri, Samsul; Gumay Febryano, Indra (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2025)
implementing various policies, including the strategy of applying a carbon tax. Although Indonesia has committed to reducing greenhouse gas emissions through carbon tax policies, the implementation of these policies by the Indonesian government has not been optimal due to the lack of specific regulations that detail the carbon tax comprehensively. Therefore, this condition warrants a deeper analysis in this study to review the carbon tax regulations established by the government in an effort to support the reduction of greenhouse gas emissions. The carbon tax in Indonesia is intended to lower greenhouse gas emissions with the aim of addressing global climate change. This tax is regulated through the 2021 Carbon Tax Law and applies to sectors with high emissions such as energy, manufacturing, and transportation, with a rate of Rp30 per kilogram of CO2e. Implementation is being carried out gradually, and the revenue from the tax will be used to fund emission reduction projects and climate change adaptation. Despite facing challenges such as industry resistance and the need for accurate measurement infrastructure, the support of various stakeholders is expected to drive the successful implementation of the carbon tax and transition towards a greener and more sustainable economy in Indonesia.